THAI CONSUMERS’ PERCEPTION AND BUYING BEHAVIOR OF HOME DECORATION PRODUCTSFROM NATURAL MATERIALS - Rattanaphan, Maneerat; Rattanaphan, Prasit; Chooset, Noppadon; Lalitsasivimol, Woraluck; Kittichonvorakun, Sinee (Journal of MCU Nakhondhat, 2025)
This research aimed to investigate consumer perception, purchasing behavior, and the factors associated with the perception and purchasing behavior of home decoration products made from natural materials. This quantitative study employed structured questionnaires to collect data from 400 Thai consumers with an average monthly income of 50,000 Baht or more, who preferred natural or uniquely crafted products. Descriptive statistics including frequency and percentage, along with the chi-square test, were used to analyze the data. The findings revealed that the majority of respondents were female, earning an average monthly income between 50,000 - 60,000 Baht, holding a bachelor’s degree, and working as business owners or self-employed. Most respondents received information about home decoration products through social media, with Facebook being the most influential platform. The most effective marketing promotion method was advertising, while marketing messages focusing on product functions and features were found to create the highest level of awareness. Video content was the most preferred type of online media. Facebook was identified as the most popular online purchasing channel, while department stores and specialty shops were the most preferred offline purchasing venues. Post-purchase behaviors commonly included reviewing products with text and images. Furthermore, the analysis showed significant relationships between gender and education level with e-marketplace purchasing channels and post-purchase behaviors. Average monthly income was related to types of offline purchasing media and post-purchase behaviors. Education level was associated with offline purchasing channels, types of online media, and online purchasing channels. Occupation was also related to marketing promotion strategies, types of social media platforms, influencers, and marketing messages.